Synthesis and characterization of a meso-anthracene-BODIPY derivative for colorimetric recognition of Cu2+ and Fe3+ - Pinto, Sónia C. S. (2021)
: Ions exist widely in biological and environmental media, and the scarcity or excess of these species can have adverse consequences. BODIPY dyes appear as heterocyclic organic compounds capable of recognizing metal ions in solution and in cells, through optical signals (colorimetric and/or fluorimetric), and their photophysical properties can be adjusted through the func-tionalization of the BODIPY core. In continuation of the work developed recently, our research group reports the synthesis of a meso-anthracene-BODIPY derivative and the respective charac-terization by 1H and 13C nuclear magnetic resonance (NMR) and UV-Vis absorption spectrosco-pies. The preliminary study of the chemosensory capacity of the BODIPY derivative was also car-ried out in the presence of several cations in acetonitrile solution, which shows a selective colori-metric response for Cu2+ and Fe3+.